Socio-Cultural Determinants of Healthcare Utilization in Rural South Punjab, Pakistan - Ahmad Ali; Dr. Muhammad Shabbir; Dr. Kamran Ashfaq (Journal for Social Science Archives, 2025)
The use of healthcare in rural Pakistan is not only determined by the accessibility of medical services, but also by the socio-cultural factors that are deeply embedded and determine healthcare-seeking behavior. The paper will look at the socio-cultural factors that influence healthcare access in rural South Punjab, Pakistan, including traditional beliefs, gender-based limitations, and family decision-making models. The quantitative cross-sectional survey design was used, and 238 adult respondents who were under treatment in three large state-owned hospitals were surveyed: Nishtar Hospital Multan, Victoria Hospital Bahawalpur, and DHQ Hospital Dera Ghazi Khan. A structured questionnaire with validated scales was used to collect data, which were analyzed with SPSS 28 and SmartPLS 4. The findings show that socio-cultural factors have a negative and significant impact on healthcare utilization. Socio-cultural factors (β= 0.38, p < .001), traditional beliefs (β= 0.29, p < .001), and gender-based restrictions (β= 0.31, p < .001) were all identified to decrease the probability to use formal healthcare services. Correlation analysis also supported the significant negative links between healthcare utilization and socio-cultural barriers, which emphasize the influence of cultural norms, stigma, and family authority on the development of health behaviors. The results indicate that the use of healthcare in rural South Punjab is heavily limited by the traditional practices, patriarchal values, and family decision-making.